The Association Of Eating Behaviour On The Growth Of Children From The Interior Districts Of Sabah,Malaysia - Eric Chee How Tan; Richard Avoi; Fredie Robinson; Mohammad Saffree Jeffree; Syed Sharizman Syed Abdul Rahim; Mohd Yusof Ibrahim; Aza Sherin Mohd Yusuff; Khamisah Awang Lukman (Taylor and Francis, 2024)
Indexed by WOS/Scopus/ERA